2017
DOI: 10.1371/journal.pone.0175055
|View full text |Cite
|
Sign up to set email alerts
|

The human body odor compound androstadienone leads to anger-dependent effects in an emotional Stroop but not dot-probe task using human faces

Abstract: The androgen derivative androstadienone is a substance found in human sweat and thus is a putative human chemosignal. Androstadienone has been studied with respect to effects on mood states, attractiveness ratings, physiological and neural activation. With the current experiment, we aimed to explore in which way androstadienone affects attention to social cues (human faces). Moreover, we wanted to test whether effects depend on specific emotions, the participants' sex and individual sensitivity to smell andros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The dot-probe task was based on standard procedures and stimulus durations used in previous research such as Holmes et al (2009) and Hornung et al (2017). Each trial in the dot-probe task consisted of a fixation cross at the center of the screen, and participants were instructed to keep their gaze on it for the complete duration of each trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dot-probe task was based on standard procedures and stimulus durations used in previous research such as Holmes et al (2009) and Hornung et al (2017). Each trial in the dot-probe task consisted of a fixation cross at the center of the screen, and participants were instructed to keep their gaze on it for the complete duration of each trial.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated, somewhat unintuitively, that response latencies were longer for fearful faces in the left visual field in the negative odor condition. Another study found no evidence for attentional effects on faces in the dot-probe task using the human body odor component androstadienone, a compound that has been suggested to affect mood states and attentional processes (Hornung et al, 2017). It should be highlighted that the facial expressions in these studies did not directly match the odor-evoked emotions, as fearful and angry faces were used, whereas unpleasant odors typically elicit disgust (Ferdenzi et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, a visual priming study using neutral faces reported no influence of androstadienone on attentional prioritization of social over nonsocial stimuli (see study 3 in Hummer and McClintock, 2009). Besides, several studies using the modified emotional Stroop task (e.g., faces with fearful and happy expressions presented with the words "happy" or "fear" written across them, Etkin et al, 2006) either found small effects on reduction of error rates, but not reaction times (Hornung et al, 2018b), reported findings limited to angry faces and to male participants (Hornung et al, 2017), or failed to find effects of androstadienone (Hornung et al, 2018a).…”
Section: General Social Cognitionmentioning
confidence: 99%
“…Despite this definition, until now, there is no clear evidence of which molecules are able to vehicle emotions, several molecules have been indicated as chemosignals, and these molecules have to be differentiated from odors and volatile substances (Table 1 and 2). Among these molecules, the testosterone metabolite androstadienone has been indicated as a putative chemosignal and suggested to be able to communicate dominance and social threat by several studies (Banner, Frumin, & Shamay‐Tsoory, 2018; Banner & Shamay‐Tsoory, 2018; Frey, Weyers, Pauli, & Mühlberger, 2012; Hornung, Kogler, Wolpert, Freiherr, & Derntl, 2017; Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%